INFORMATION TECHNOLOGIES IN ACCOUNTING AND AUDIT - KUDLAI, Albina; BELOZERTSEV, Vasil’ (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Each company operates to maximize profits, so the main task is to reduce costs, which can be achieved by reducing production costs, increasing staff productivity, increasing control over the level of costs and more. Among these methods, the most effective over the years is the automation of accounting. Accounting is a complex system that requires accuracy, timeliness, thoroughness, analysis and planning.The purpose of the article is to determine the need for the introduction of information technology in the organization of accounting and auditing; comparison of computer programs.The research is based on methods of economic theory, dialectical method of scientific knowledge and general scientific methods of knowledge: methods of theoretical generalization, analysis and synthesis.The study conducted research on the need for the introduction of information technology in the work of accountants and auditors. The positive and negative consequences of the implementation of automated programs were considered. The article compares computer programs of accounting and auditing. We have come to the conclusion that all programs have both disadvantages and advantages. Therefore, business leaders must decide on the program that is most optimal for their business activities, and auditors - with a program that will ensure effective audit.
Keywords: accounting; audit; Information Technology; automated credential processing